Enhancing the Interest of Undergraduate Students in Geometry Through GeoGebra-Assisted Instruction in Colleges of Education, Ghana - Wonu, Nduka; Kakraba, Eric Quarshie; Auwal, Mamman Musa (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2024)
In a College of Education located in the Volta region of Ghana, this study investigated the impact of GeoGebra-supported teaching on the interest for learning geometry among undergraduate students. Employing a non-equivalent control group pre-test post-test quasi-experimental research design, the study formulated two research questions and two hypotheses to guide its investigation. The sample comprised 73 undergraduate mathematics students, with 38 students in the experimental group and 35 in the control group. Data collection utilized the Geometry Interest Inventory (GII), which was validated by experts, with a calculated Cronbach's alpha coefficient of 0.85 indicating its reliability. Analysis of Covariance (ANCOVA) was employed to test the hypotheses at a significance level of 0.05, while mean and standard deviation were used to analyze data for addressing the research questions. Results indicated that students taught geometry with GeoGebra demonstrated significantly greater interest in the subject compared to those taught with diagrams. Furthermore, the study found that both male and female students exhibited similar levels of interest in geometry when taught using GeoGebra-supported instruction. It was recommended among others that in colleges of education, GeoGebra-assisted instruction should be utilized to spark students' enthusiasm in learning geometry, regardless of gender.